2022
DOI: 10.1007/s00380-022-02119-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgical explantation of failed transcatheter heart valves: indications and results

Abstract: Given the recent surge in transcatheter heart valve replacement (THVR), cardiac surgeons will surely face the challenge of eventual explantation. The aim of this study was to determine indications for reoperation, while exploring pertinent technical aspects and survival after THV explantation in a cohort originally deemed high risk or even inoperable. Between February 2008 and March 2019, 31 patients with failed transcatheter aortic valve replacement (TAVR) underwent surgical explantations at our facility. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…After removal of duplicate entries, 459 articles were screened, of which 432 were excluded on the basis of titles and abstracts; a total of 26 relevant publications were retrieved for further assessment. Twelve studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], analysing a total of 1584 participants receiving TAVR explant, met the inclusion criteria and were included in the quantitative analysis. A summary of the characteristics of the studies included is reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicate entries, 459 articles were screened, of which 432 were excluded on the basis of titles and abstracts; a total of 26 relevant publications were retrieved for further assessment. Twelve studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ], analysing a total of 1584 participants receiving TAVR explant, met the inclusion criteria and were included in the quantitative analysis. A summary of the characteristics of the studies included is reported in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Summary of the main results from the systematic review. Forest plots tables for the outcomes of mortality, stroke, and renal failure, with metaregression plots below exploring the relationship between these outcomes and the ratio between self-expandable and balloon-expandable valves in the studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. CI—confidence interval .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the incidence of surgical re-intervention post-TAVR. The overall incidence of operative interventions after TAVR was 0.4% in Michigan state as reported by Brescia et al [12], 1% in a report by Fukuhara et al from the University of Michigan [13], and 1.2% in a report by Muensterer et al from Munich [14]. Jawitz et al [15] in an analysis of the STS database estimated that the incidence of surgery after TAVR in the US is 0.3% nationwide.…”
Section: Patient Profile and Indicationsmentioning
confidence: 89%